Reforming the health sector in developing countries : the central role of policy analysis. - WALT, Gill (1994)
Argues that much health policy wrongly focuses attention on the content of reform, thus diverting attention from understanding the processes why desired policy outcomes fail to emerge. Stresses the need for greater emphasis on policy analysis, and urges that more attention be paid to the actors involved in policy reform (at the international, national and sub-national levels), the processes contingent on developing and implementing change, and, the context within which policy is developed.